Czy muzyka jest ucieleśnieniem matematyki? Analiza przypadku introitu Statuit - Mycka, Agnieszka; Mycka, Jerzy (Filozofia Nauki, 2012)
The article starts with various definitions of music and its components (taken es-pecially from medieval sources). Then the Statuit introit is presented as the main example useful for mathematical analysis in the paper. We discuss the distinc-tion between a musical work and its performance and give a review of possible representations/ notations of music with their short mathematical characteristics. The next point is devoted to the concept of modality, Gregorian scales and selected theories linking musical experience with mathematics. We use the Statuit introit as the illustration for the construction of its statistical analysis (for notes, intervals and progresses). The results of this analysis serve as a reference point to indicate the connection between the process of musical composition and the apparatus of mathematical linguistics. Based on the above considerations we suggest that the pattern analysis could be useful as a tool unifying some aspects of music and mathematics and explaining the perception of musical works.